PENERAPAN MAKE A MATCH UNTUK MENINGKATKAN AKTIVITAS BELAJAR MATA PELAJARAN EKONOMI SMAS MUJAHIDIN PONTIANAK - Sari, Atna; Asriati, Nuraini; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to purpose the increase in student learning activities in SMA Swasta Mujahidin Pontianak use the Make A Match learning model. The research method used is an experimental research with a quantitative form. The subjects in this study were students of class XI IPS 1 and XI IPS 2 SMA Swasta Mujahidin Pontianak with 69 students. The source of the data of this study was the students of class XI IPS and the data were observation sheets of student learning activities and documentation. data collection instruments in this study observation sheets of student activity and documentation. The results showed that there was an increase in student learning activities of the first meeting with the second meeting with an average of 58,23% to 66,58% in the experimental class that  quiet as good. and the results of the control class of the first and second meetings have increased but are still classified as less with an average learning activity is 35.93% increased to 38.85% .so the application of the make a match type of cooperative learning model can increase the learning activities of students in economic class XI SMA Swasta Mujahidin Pontianak. Keywords: Make A Match, Student Learning Activities, Economic Subjects